Children's sleep patterns from 0 to 9 years: Australian population longitudinal study. Issue 2 (16th December 2013) - Price, Anna M H; Brown, Judith E; Bittman, Michael; Wake, Melissa; Quach, Jon; Hiscock, Harriet
Abstract : Objective: To provide accurate population normative data documenting cross-sectional, age-specific sleep patterns in Australian children aged 0–9 years. Design and setting: The first three waves of the nationally representative Longitudinal Study of Australian Children, comprising two cohorts recruited in 2004 at ages 0–1 years (n=5107) and 4–5 years (n=4983), and assessed biennially. Participants: Children with analysable sleep data for at least one wave. Measures: At every wave, parents prospectively completed 24-h time-use diaries for a randomly selected week or weekend day. 'Sleeping, napping' was one of the 26 precoded activities recorded in 15-min time intervals. Results: From 0 to 9 years of age, 24-h sleep duration fell from a mean peak of 14 (SD 2.2) h at 4–6 months to 10 (SD 1.9) h at 9 years, mainly due to progressively later mean sleep onset time from 20:00 (SD 75 min) to 21:00 (SD 60 min) and declining length of day sleep from 3.0 (SD 1.7) h to 0.03 (SD 0.2) h. Number and duration of night wakings also fell. By primary school, wake and sleep onset times were markedly later on weekend days. The most striking feature of the centile charts is the huge variation at all ages in sleep duration, sleep onset time and, especially, wake time in this normal population. Conclusions: Parents and professionals can use these new centile charts to judge normalcy of children's sleep. In future research, these population parameters will now be used to empirically determine optimal child sleep patterns for child and parent outcomes like mental and physical health.